2019
DOI: 10.1002/ardp.201800213
|View full text |Cite
|
Sign up to set email alerts
|

Chemical structure modifications and nano‐technology applications for improving ADME‐Tox properties, a review

Abstract: The chemical structure of a drug molecule affects its physicochemical properties and subsequent biological activities. Many pharmacologically active molecules fail to reach the market or have an inconvenient route of administration due to their chemical structure. This is especially important with the recent tendency to develop drug candidates beyond the drug-likeness space for addressing difficult targets such as protein-protein interfaces. The objective of this review is to discuss chemical and pharmaceutica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 154 publications
0
6
0
Order By: Relevance
“…7a presents Cur broad spectra with a noted absorbance maximum at B420 nm due to low-energy p-p* excitation, matching well with the reported work. 34,80 For the waterbased systems, the amounts of Cur absorbed in F38, F68, F88, F98, and F108 without glucose micelles are 0.9 mg mL À1 , 1.2 mg mL À1 , 1.6 mg mL À1 , 1.7 mg mL À1 and 1.9 mg mL À1 , respectively, which are more than the reported solubility value of Cur in water (0.6 mg mL À1 ). 27 This reflects the novelty of this work.…”
Section: Spectral Validationmentioning
confidence: 91%
See 2 more Smart Citations
“…7a presents Cur broad spectra with a noted absorbance maximum at B420 nm due to low-energy p-p* excitation, matching well with the reported work. 34,80 For the waterbased systems, the amounts of Cur absorbed in F38, F68, F88, F98, and F108 without glucose micelles are 0.9 mg mL À1 , 1.2 mg mL À1 , 1.6 mg mL À1 , 1.7 mg mL À1 and 1.9 mg mL À1 , respectively, which are more than the reported solubility value of Cur in water (0.6 mg mL À1 ). 27 This reflects the novelty of this work.…”
Section: Spectral Validationmentioning
confidence: 91%
“…[84][85][86] Though poor water solubility and low absorption in the human body are major limitations facing Cur, recent research has demonstrated that the drawbacks of Cur can be effectively addressed when it is integrated into Pluronic sbased micellar nanocarriers. 80,86 Spectral studies of the examined system revealed an enhancement in the solubility of the waterinsoluble drug Cur in conjunction with the BCP micelles (Fig. 7).…”
Section: Spectral Validationmentioning
confidence: 95%
See 1 more Smart Citation
“…In recent years, numerous drug delivery systems, including liposomes, micelles, “smart” polymers, and hydrogels, have been developed for cancer therapy [ 547 552 ]. For instance, to achieve accurate delivery to mitochondria with high specificity and low size, a native genetic system encoded in Salmonella pathogenicity island-1 (SPI-1) was used by Lim et al [ 553 ].…”
Section: Strategies For Overcoming Mitochondria-targeting Bottlenecks...mentioning
confidence: 99%
“…This is especially important given the recent trend to develop drug candidates out of space similar to drugs to deal with difficult target proteins due to the need for linkage between proteins. The aim of the in silico research is to conduct an accurate study with chemical and pharmaceutical approaches so that drug candidates are known to have good ADME-Tox properties and high bioavailability [11].…”
Section: Discussionmentioning
confidence: 99%